PENGARUH KEPUASAN KERJA DAN JOB INSECURITY TERHADAP TURNOVER INTENTION KARYAWAN PADA PT. ALNO AGRO UTAMA - Nita Puji Rahayu; Marliza Ade Fitri (UM. Bengkulu, 2022)
This study aims to determine the effect of job satisfaction and job insecurity on employee turnover intention at PT. Alno Agro Utama either partially or simultaneously. There are several independent variables (x) that will be discussed in this study, including job satisfaction and job insecurity which are the objects in this study are employees at PT. Alno Agro Utama, totaling 105 people. In this study, there are several data analysis techniques used, including using instrument tests, classical assumption tests, analysis of respondents' responses, multiple linear regression analysis, determinant coefficients, and also hypothesis testing. From the results of multiple linear regression, the regression equation is as follows: Y = 2.754 - 0.198 (X1) + 0.479 (X2). The results of the t-test on the job satisfaction variable (X1), show t count > t table, namely (-2.711 > 1.98472) and sig < a (0.010 < 0.050). Job Insecurity (X2), shows t count > t table, namely (2.891 > 1.98472) and sig < a (0.003 < 0.050). The results of the F test show that Fcount > Ftable, (96.918 > 3.088) and sig < a (0.000 < 0.050). From the results of the tests that have been carried out, it can be concluded that the variables of Job Satisfaction and Job Insecurity have a partial or simultaneous effect on Employee Turnover Intention at PT. Alno Agro Utama. Keywords : Job Satisfaction, Job Insecurity and Turnover Intention